2006
DOI: 10.2166/wqrj.2006.039
|View full text |Cite
|
Sign up to set email alerts
|

Pharmaceuticals and Endocrine Disruptors in Wastewater Treatment Effluents and in the Water Supply System of Calgary, Alberta, Canada

Abstract: Due to a growing interest in the occurrence of pharmaceutically active compounds (PhACs) and endocrine disrupting compounds (EDCs) in the aquatic environment and their potential impacts on humans and the environment, a collaborative study was conducted on these emerging contaminants in the effluents from the wastewater treatment plants (WWTPs) and in the drinking water supply system of Calgary, Alberta. A number of PhACs and EDCs were detected in the WWTP effluents, at concentrations ranging from ng/L to low µ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
3
7

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(59 citation statements)
references
References 65 publications
5
44
3
7
Order By: Relevance
“…123 O bioensaio denominado YES, desenvolvido por Routledge e Sumpter em 1996, 194 vem sendo largamente utilizado para a avaliação da atividade estrogênica 195 de amostras ambientais tais como efluentes de ETE, [196][197][198][199] águas superficiais 9,51,93,200 e água tratada, 19,20 bem como para avaliar a eficiência de diferentes tipos de tratamento de efluentes. 196,[201][202][203] No Brasil, Sanchez confirmou a indução de vitelogenina por E2 e EE2 em peixes machos (Rhamdia quelen) nativos da região do Paraná. 204 Bergamasco e colaboradores reportaram a maior sensibilidade do bioensaio BLYES quando comparada às análises químicas por LC-MS/MS ao estudar quatro diferentes mananciais (Represa de Tanque Grande, Rio Atibaia, Rio Sorocaba e Rio Cotia) no Estado de São Paulo.…”
Section: O Aspecto Regulatóriounclassified
“…123 O bioensaio denominado YES, desenvolvido por Routledge e Sumpter em 1996, 194 vem sendo largamente utilizado para a avaliação da atividade estrogênica 195 de amostras ambientais tais como efluentes de ETE, [196][197][198][199] águas superficiais 9,51,93,200 e água tratada, 19,20 bem como para avaliar a eficiência de diferentes tipos de tratamento de efluentes. 196,[201][202][203] No Brasil, Sanchez confirmou a indução de vitelogenina por E2 e EE2 em peixes machos (Rhamdia quelen) nativos da região do Paraná. 204 Bergamasco e colaboradores reportaram a maior sensibilidade do bioensaio BLYES quando comparada às análises químicas por LC-MS/MS ao estudar quatro diferentes mananciais (Represa de Tanque Grande, Rio Atibaia, Rio Sorocaba e Rio Cotia) no Estado de São Paulo.…”
Section: O Aspecto Regulatóriounclassified
“…Caffeine levels were also investigated in different source waters from Lisbon, Portugal, by de Jesus Gaffney et al 40 The authors observed concentrations ranging from 30 to 46 ng L -1 in the rivers Tagus and Zêzere with highest levels credited to the discharge of WWTP effluents. In the region of Calgari, Canada, Chen et al 41 reported caffeine concentrations varying from 43 to 160 ng L -1 in the Bow River. Since sampling point was located upstream of the local WWTP, authors suggested that caffeine, as well as other pharmaceutically active compounds, entered the river through alternative pathways, such as improper discharges and/or private septic systems.…”
Section: Emerging Contaminants In Source and Drinking Watersmentioning
confidence: 99%
“…La presencia de MC en el agua superficial se ha atribuido a la descarga de aguas residuales y a la baja eficiencia de eliminación de los sistemas de tratamiento convencionales (Westerhoff et al 2005, Chen et al 2006, Hernando et al 2006, Zhou et al 2012. Esto resulta inconveniente para Colombia, donde se estima que sólo el 36 % de las aguas residuales domésticas urbanas son tratadas (DNP 2016).…”
Section: Introductionunclassified
“…En el agua potable, la presencia de MC se atribuye a que las plantas de tratamiento de agua potable (PTAP) convencionales no garantizan su completa eliminación por lo que se han reportado compuestos como la iopromida, ibuprofeno, carbamazepina y bisfenol A (BPA) en el agua potable (Westerhoff et al 2005, Chen et al 2006, Kim et al 2007). …”
Section: Introductionunclassified